Diagnostic Dilemma in Abdominal Pregnancy - A Case Report - Afroz, Laila; Chowdhury, Shiuly; Mazhar, Syed Iqbal (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Advanced abdominal pregnancy is a very rare and complex condition demanding challenging management. High index of suspicion may reduce the diagnostic error. Maternal mortality and morbidity is high and fetal outcome is poor. The key to favorable maternal outcome is early diagnosis and management. A case of 37 weeks abdominal pregnancy with fetal death has been reported here. The patient was repeatedly admitted in the Gynae and Obstetric department in different units for unusual abdominal discomfort beginning from 20th weeks of pregnancy. But the diagnosis had been missed everytime. Finally, she reported with 37th week's pregnancy with intra-uterine fetal death. With high index of suspicion ultrasonography was done by an Obstetrician in the department which gave the diagnosis and was confirmed by laparotomy. DOI:10.3329/jbcps.v27i3.4298 J Bangladesh Coll Phys Surg 2009; 27: 177-180